Structural Health Monitoring of Bridges with Fiber Bragg Grating Sensors - Navarro-Henríquez, Francisco (2014)
This paper describes part of the initial studies in the research project eBridge 2.0: integrated bridge system performance. Systems with fiber optic sensors FBG (Fiber Bragg Grating) are consolidated in the Structural Health Monitoring (SMH) of bridges, Nondestructive Testing (NDT) static and dynamic measurements of deformation, displacement, deflection, temperature and vibration. This article provides a brief introduction to the technology and the fundamentals of fiber optic sensors, also present comparative advantages over its traditional counterpart is presented. Their characteristics are described and measurement graphics are presented as an application example of the FBG sensors. Finally, some key aspects to consider for proper use in the field are mentioned.